Do Health Expenditures Converge Among ASEAN Countries? - Li, Zheng-Zheng; Liu, Guangzhe; Tao, Ran; Lobont, Oana-Ramona (Frontiers in Public Health, 2021)
This paper aims to determine the existence of convergence in health expenditures among Association for South East Asian Nations (ASEAN) countries. Based on the SPSM procedure and panel KSS unit root test results, the public health expenditures (PUHE) in Indonesia, Lao PDR, Cambodia, the Philippines, and Myanmar are converging, while that of Brunei Darussalam, Malaysia, Vietnam, Singapore, and Thailand are diverging. In addition, the sequences of private health expenditures (PRHE) in ASEAN member states are stationary, which implies convergence. This finding is in accordance with Wagner's law, that is, as nations develop, they are forced to expand public expenditure. Specifically, countries with low levels of PUHE tend to catch up with the high health spending countries. This research has policy implications with regard to the convergence of health expenditure across countries. The government in low- and lower-middle income countries should raise PUHE to provide access to health services for those who are unaffordable individuals.